Shakespeare and Spenser : attractive opposites - Lethbridge, J. B., 1958-; Anderson, Judith H.; Cheney, Patrick, 1949-; Hays, Michael L. (Michael Louis), 1940-; Hile, Rachel E.; Horton, Ronald Arthur, 1936-; Lethbridge, J. B., 1958-; Nelson, Karen; Oldrieve, Susan; Prescott, Anne Lake, 1936-; Reid, Robert Lanier, 1943- (Manchester Spenser., 2008)
In these 10 original papers by experts on the relations between Spenser and Shakespeare, the subject of the linguistic borrowings of Shakespeare from Spenser is treated systematically leading into broader-scale borrowings and influences being considered. A large bibliography of previous work is also provided.